Cu(i) stabilizing crosslinked polyethyleneimine. Issue 28 (28th July 2015) - Movahedi, Alireza; Lundin, Angelica; Kann, Nina; Nydén, Magnus; Moth-Poulsen, Kasper
<x xml:space="preserve">Abstract</x> With the aim to regulate the coordination environment of Cu(i) and Cu(ii) ions, we have prepared a triazole dialdehyde crosslinking agent with 'soft' coordination that can crosslink PEI via indirect reductive amination.